Automated microfluidic screening of ligand interactions during the synthesis of cesium lead bromide nanocrystals. Issue 6 (2nd March 2020) - Li, Shangkun; Baker, Robert W.; Lignos, Ioannis; Yang, Zhibo; Stavrakis, Stavros; Howes, Philip D.; deMello, Andrew J.
Abstract : Automated microfluidic reaction parameter scanning reveals optimal conditions for bright and narrow emission from cesium lead bromide nanocrystals. Abstract : Varying the nature of the molecular surface ligands used to synthesize and stabilize lead halide perovskite nanocrystals provides a facile way of tuning and optimizing particle properties. However, the inherently complex reaction parameter space associated with perovskite nanocrystal synthesis complicates this, necessitating long-term and laborious experimentation to optimize conditions for a specific ligand set, and to compare nanoparticle properties across different ligand sets. In the current work, we present an automated microfluidic-based strategy for multidimensional parameter screening, seeking to maximize luminescence intensities and minimize emission bandwidths from quantum confined nanostructures, by monitoring variations in photoluminescence as a function of reaction temperature, base-to-acid ligand ratio, and ligand alkyl chain structure (linear versus branched). For a linear ligand pair (octylamine and octanoic acid), we find two reaction parameter sets that yield bright and narrow emission from nanosheets emitting at 460 nm (synthesized at 100 °C with a low base : acid ratio, FWHM = 25 nm) and nanowires emitting at 497 nm (synthesized at 140 °C with a high base : acid ratio, FWHM = 17 nm). Introducing branched ligands (2-ethylhexylamine and/or 2-ethylhexanoic acid) induces a red shift in emission and shows that bright and narrow emission can only be obtained from weakly quantum-confined nanostructures, within the reaction conditions studied. This work represents the first use of a rapid automated microfluidic system for the screening of ligand interactions during the synthesis lead halide perovskite nanocrystals.